Recombinant fibrous protein biomaterials meet skin tissue engineering - Li, Dipeng; Wang, Yirong; Zhu, Shan; Hu, Xuezhong; Liang, Renjie (Frontiers in Bioengineering and Biotechnology, 2024)
Natural biomaterials, particularly fibrous proteins, are extensively utilized in skin tissue engineering. However, their application is impeded by batch-to-batch variance, limited chemical or physical versatility, and environmental concerns. Recent advancements in gene editing and fermentation technology have catalyzed the emergence of recombinant fibrous protein biomaterials, which are gaining traction in skin tissue engineering. The modular and highly customizable nature of recombinant synthesis enables precise control over biomaterial design, facilitating the incorporation of multiple functional motifs. Additionally, recombinant synthesis allows for a transition from animal-derived sources to microbial sources, thereby reducing endotoxin content and rendering recombinant fibrous protein biomaterials more amenable to scalable production and clinical use. In this review, we provide an overview of prevalent recombinant fibrous protein biomaterials (collagens, elastin, silk proteins and their chimeric derivatives) used in skin tissue engineering (STE) and compare them with their animal-derived counterparts. Furthermore, we discuss their applications in STE, along with the associated challenges and future prospects.